The Libros Imposibles Collection (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The Libros Imposibles Collection is the creation of two poets, Floriano Martins (Brazil) and Juana M. Ramos (El Salvador). What makes a book to be considered impossible is not only its unrealizable condition, in this case in editorial terms, but its incredible character, an extraordinary object. The collection seeks to address both aspects: books that for some reason did not find a publisher, along with those that, despite their importance, did not receive the diffusion they deserved, in addition to some anthologies that were gathered for this occasion. There are books of different genres: poems, prose, novels, essays, interviews, and even a special feature: the inclusion of books written jointly. Translated with DeepL.com (free version)
Keywords: Libros Imposibles; Poetry